Clinical characteristics of Japanese patients with moderate to severe COVID-19. Issue 6 (June 2021) - Otoshi, Ryota; Hagiwara, Eri; Kitayama, Takaaki; Yamaya, Takafumi; Higa, Katsuyuki; Murohashi, Kota; Sato, Yozo; Tabata, Erina; Shintani, Ryota; Okabayashi, Hiroko; Ikeda, Satoshi; Niwa, Takashi; et al.
Abstract: Introduction: Although several reports on the risk factors for severe disease of COVID-19 already exist, reports on effective early indicators are still limited, especially from Japan. This study was conducted to clarify the patient's characteristics whose disease progressed to severe status. Methods: The medical records of all consecutive 300 Japanese patients hospitalized at our institution between February and November 2020 were retrospectively reviewed. The clinical characteristics were evaluated to compare between mild (no oxygen needed), moderate (oxygen needs of 1–4 L/min), and severe diseases (oxygen needs of 5 L/min or more). Results: The median age was 68 years old, with 123 (41.0%) males and 177 (59.0%) females. Of these, 199 patients (66.3%), 55 patients (18.3%), 46 patients (15.3%) patients were in the mild disease, moderate disease, severe disease groups, respectively. Patients with severe disease were more likely to be older, have more comorbidities, and tended to have higher body mass index. In laboratory data, lymphocyte count, levels of C-reactive protein (CRP), LDH, and AST on admission were significantly associated with the severity. In multivariate analysis, age and CRP were the independent risk factors for severe disease (OR = 1.050, 1.130, respectively). The optimal cut-off value for age was 74 years old and that for CRP was 3.15 mg/dL. Conclusions: Age and CRP were independently associated with disease severity of COVID-19 in multivariate analysis. Additionally, the numbers of underlying disease, lymphocyte count, and inflammatory markers such as LDH and D-dimer may also be related to disease severity.